2019
DOI: 10.1002/wer.1068
|View full text |Cite
|
Sign up to set email alerts
|

Bone‐derived biochar and magnetic biochar for effective removal of fluoride in groundwater: Effects of synthesis method and coexisting chromium

Abstract: The presence of fluoride in groundwater in excess of 1.5 mg L−1 is a major environmental health concern, and biochar is a promising low‐cost adsorbent for the treatment of such water. In the present study, pristine and magnetic biochars were synthesized by peanut hull and bovine bone for the adsorption of fluoride. The biochars were systematically characterized by SEM‐EDS, BET, XRD, VSM, FT‐IR, and XPS. The experiment results showed that the magnetic biochar prepared by soaking biomass in FeCl3 solution and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…In particular, a cooling agent used in scientific instruments commercially known as Galden ® -IUPAC name is oxidized poly(1,1,2,3,3,3-hexafluoroprop-1-ene)-with formula CF 3 − (OCF(CF 3 )CF 2 ) n − (OCF 2 ) m − OCF 3 and an average molecular weight of 610 Da, can be adsorbed on biochar's surface by (i) charge transfer bond with biochar metal impurities; (ii) H-bonds with biochar surface hydrophilic groups; (iii) Van der Waals interactions with the biochar C-skeleton; (iv) outer-sphere interactions where water molecules bridge the Galden ® with the electronpoor biochar metal impurities. Biochar can also trap anionic pollutants such as fluoride (F − ) in groundwater [214]. In this case, the presence of biochar surface cation impurities is considered responsible for F − electrostatic entrapment.…”
Section: The Mechanisms Of Entrapment and Decomposition Of Pollutants In Biocharmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, a cooling agent used in scientific instruments commercially known as Galden ® -IUPAC name is oxidized poly(1,1,2,3,3,3-hexafluoroprop-1-ene)-with formula CF 3 − (OCF(CF 3 )CF 2 ) n − (OCF 2 ) m − OCF 3 and an average molecular weight of 610 Da, can be adsorbed on biochar's surface by (i) charge transfer bond with biochar metal impurities; (ii) H-bonds with biochar surface hydrophilic groups; (iii) Van der Waals interactions with the biochar C-skeleton; (iv) outer-sphere interactions where water molecules bridge the Galden ® with the electronpoor biochar metal impurities. Biochar can also trap anionic pollutants such as fluoride (F − ) in groundwater [214]. In this case, the presence of biochar surface cation impurities is considered responsible for F − electrostatic entrapment.…”
Section: The Mechanisms Of Entrapment and Decomposition Of Pollutants In Biocharmentioning
confidence: 99%
“…However, the effect of these impurities reduces as pH increases. In fact, Zhou et al [214] observed that the higher the pH, the lower the amount of fluoride retained on the biochar surface. This can be explained by the progressive deprotonation of the surface acidic functional groups which allow negative charge to increase and electrostatic repulsions.…”
Section: The Mechanisms Of Entrapment and Decomposition Of Pollutants In Biocharmentioning
confidence: 99%
See 1 more Smart Citation
“…Adsorption mechanism of both adsorbates (i.e., fluoride and nitrate) implied the hydrogen bond formation with the participation of protonated surface hydroxyls on the iron oxides. BCs and their magnetic versions were prepared with bovine bone and peanut hull for fluoride adsorption [162]. XPS, FTIR, XRD, SEM-EDX, and VSM were used to analyze the surface chemistry and magnetic properties of these adsorbents.…”
Section: 4mentioning
confidence: 99%
“…A variety of conventional methods have been employed for the removal of fluoride, including electrolysis (Amor et al, 2001), ion exchange (R. X. Liu et al, 2002), chemical precipitation (M. Yang et al, 2001), membrane filtration (Tahaikt et al, 2007), and adsorption (Z. L. He et al, 2013; P. Li et al, 2014). Among them, adsorption method is commonly viewed as the most promising method for removal of fluoride due to its advantages of high efficiency, low cost, and easy operation (Jagtap et al, 2012; Zhou et al, 2019). As an adsorbent, metal oxides can be used as good fluoride capture agents because of their positive electric properties.…”
Section: Introductionmentioning
confidence: 99%